An experimental investigation of the influence of inter-turbine spacing on the loads and performance of a co-planar tidal turbine fence. (April 2023) - McNaughton, J.; Ettema, S.; Zilic de Arcos, F.; Vogel, C.R.; Willden, R.H.J.
Abstract: Multi-rotor tidal turbine systems offer engineering benefits through shared infrastructure and improved opportunities for maintenance. Additionally, the ability to specify accurately the inter-turbine spacing in co-planar arrays allows rotors to be designed and deployed to benefit from the constructive interference effects available from neighbouring rotors. In this work we consider the effect of inter-turbine spacing and control of this spacing for a fence of turbines in low overall levels of global blockage (4.5%). We conduct experiments in a towing tank using two tidal turbine models that were previously designed to benefit from constructive interference effects at high local blockage, i.e. close inter-turbine spacing. The turbines were towed in a side-by-side configuration by suspending them from above. By making use of the tank's side wall to act as a symmetry plane we were able to emulate a fence of four laterally arrayed turbines. As indicated by theory, decreasing inter-turbine spacing is shown to have a positive effect on fence performance. By reducing the inter-turbine spacing from one diameter to a quarter of a diameter, we observe an overall 1.4% performance increase, which is driven by a 2.8% increase in the inboard turbine's power coefficient. This research is a first attempt to quantify constructive interference effects for a four turbine fence; the methods and results will be used to instruct further studies to aid the development of such multi-rotor tidal turbine systems. Graphical abstract: Highlights: Experimental study of a four-turbine tidal turbine fence in a towing tank. Demonstration of performance gains through reducing inter-turbine spacing. Loading asymmetry between inboard and outboard rotors in a multi-rotor fence.